Multi‐Omics Analysis of Gut Microbiome and Host Metabolism in Different Populations of Chinese Alligators (alligator sinensis) During Various Reintroduction Phases - Chong Wang; Changcheng Li; Fuyong You; Yongkang Zhou; Genjun Tu; Ruoya Liu; Pingsi Yi; Xiaobing Wu; Haitao Nie (Ecology and Evolution, 2025)
ABSTRACT Reintroduction plays a significant role in the self‐maintenance and reconstruction of wild animal populations, serving as a communication bridge between captive and wild animals. The Chinese alligator (Alligator sinensis) is a distinct and endangered reptile species found in China. The mechanisms by which artificially bred Chinese alligators adapt following their release into the wild remain poorly understood. This study aims to elucidate the alterations in gut microbiomes and metabolic phenotypes of Chinese alligators during their reintroduction. During the Chinese alligator's reintroduction, Fusobacterium and Cetobacterium became more abundant, while typical pathogens declined significantly. The gut type of the Chinese alligator changed from Acinetobacter to Cetobacterium. The construction of the gut microbial community was dominated by neutral (random) processes and shifted towards deterministic processes with the progression of reintroduction. In terms of species function, reintroduction significantly upregulated the expression of host immune‐related genes and significantly decreased the expression of gut bacterial pathogenic genes and antibiotic resistance genes. Metagenomic and metabolomic KEGG enrichment analyses indicate that glucoside hydrolase families 13 and 23—alongside glycolysis and gluconeogenesis pathways—may play pivotal roles in energy metabolism, host‐pathogen interactions, and homeostasis maintenance for Chinese alligators. Differential metabolite analysis identified significant upregulation of metabolites related to neuroendocrine immune modulation and significant down‐regulation of anti‐inflammatory metabolites during Chinese alligator reintroduction. Association analysis showed that there were significant co‐metabolic effects between microorganisms and metabolites, which coordinated host adaptive interaction. This study provides insights into the synergistic mechanisms of host adaptation and wild environment adaptation for Chinese alligators.